Advanced Bioresponsive Multitasking Hydrogels in the New Era of Biomedicine. (18th July 2021) - Niazi, Mostafa; Alizadeh, Effat; Zarebkohan, Amir; Seidi, Khaled; Ayoubi‐Joshaghani, Mohammad Hosein; Azizi, Mehdi; Dadashi, Hamed; Mahmudi, Hossein; Javaheri, Tahereh; Jaymand, Mehdi; Hamblin, Michael R.; Jahanban‐Esfahlan, Rana; et al.
Abstract: Advanced forms of hydrogels have many inherently desirable properties and can be designed with different structures and functions. In particular, bioresponsive multifunctional hydrogels can carry out sophisticated biological functions. These include in situ single‐cell approaches, capturing, analysis, and release of living cells, biomimetics of cell, tissue, and tumor‐specific niches. They can allow in vivo cell manipulation and act as novel drug delivery systems, allowing diagnostic, therapeutic, vaccination, and immunotherapy methods. In the present review of multitasking hydrogels, new approaches and devices classified into point‐of‐care testing (POCT), microarrays, single‐cell/rare cell approaches, artificial membranes, biomimetic modeling systems, nanodoctors, and microneedle patches are summarized. The potentials and application of each format are critically discussed, and some limitations are highlighted. Finally, how hydrogels can enable an "all‐in‐one platform" to play a key role in cancer therapy, regenerative medicine, and the treatment of inflammatory, degenerative, genetic, and metabolic diseases is being looked forward to. Abstract : Bioresponsive multitasking hydrogels can play a key role in cancer therapy, regenerative medicine, and the treatment of inflammatory, degenerative, genetic, and metabolic diseases. These hydrogels are classified into point‐of‐care testing, microarrays, single‐cell/rare cell approaches, artificial membranes, biomimetic modeling systems, nanodoctors, and microneedle patches.